Rolls of Northamptonshire sessions of the peace : roll of the supervisors, 1314-1316 : roll of the keepers of the peace, 1320 - Gollancz, Marguerite (Publications of the Northamptonshire Record Society, 1940)
Transcripts and lists of supervisors, keepers of the peace and justices of gaol delivery.